Knockdown of microRNA-135b in Mammary Carcinoma by Targeted Nanodiamonds: Potentials and Pitfalls of In Vivo Applications - Křivohlavá, Romana; Neuhӧferová, Eva; Jakobsen, Katrine Q; Benson, Veronika (Nanomaterials (Basel, Switzerland), 2019)
Nanodiamonds (ND) serve as RNA carriers with potential for in vivo application. ND coatings and their administration strategy significantly change their fate, toxicity, and effectivity within a multicellular system. Our goal was to develop multiple ND coating for effective RNA delivery in vivo. Our final complex (NDA135b) consisted of ND, polymer, antisense RNA, and transferrin. We aimed (i) to assess if a tumor-specific coating promotes NDA135b tumor accumulation and effective inhibition of oncogenic microRNA-135b and (ii) to outline off-targets and immune cell interactions. First, we tested NDA135b toxicity and effectivity in tumorospheres co-cultured with immune cells ex vivo. We found NDA135b to target tumor cells, but it binds also to granulocytes. Then, we followed with NDA135b intravenous and intratumoral applications in tumor-bearing animals in vivo. Application of NDA135b in vivo led to the effective knockdown of microRNA-135b in tumor tissue regardless administration. Only intravenous application resulted in NDA135b circulation in peripheral blood and urine and the decreased granularity of splenocytes. Our data show that localized intratumoral application of NDA135b represents a suitable and safe approach for in vivo application of nanodiamond-based constructs. Systemic intravenous application led to an interaction of NDA135b with bio-interface, and needs further examination regarding its safety.
Keywords: cancer cell targeting; nanodiamond; antimiR; targeted nanoparticles; nano-bio interaction; in vivo application